2006
DOI: 10.1002/art.22359
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell arteritis: Involvement of intracranial arteries

Abstract: To determine the occurrence and frequency of central nervous system (CNS) vasculitis in GCA, we reviewed the medical records of all patients with a diagnosis of CNS vasculitis or angiitis at the Mayo Clinic (Rochester, MN) over a 17-year period and identified those with both biopsy-proven GCA and pathologic and/or angiographic evidence of intracranial vasculitis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
100
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 40 publications
2
100
0
6
Order By: Relevance
“…18,19,23,29 Nevertheless, most of these patients did not undergo an MR imaging examination including sequences adapted for evaluation of intracranial VWE. 6,11 Moreover, postmortem examination can only be performed in patients with GCA with lethal complications (eg, cerebrovascular ischemic events) but not systematically. In addition, postmortem analysis in patients with GCA cannot guarantee an acute state of inflammation of the analyzed tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19,23,29 Nevertheless, most of these patients did not undergo an MR imaging examination including sequences adapted for evaluation of intracranial VWE. 6,11 Moreover, postmortem examination can only be performed in patients with GCA with lethal complications (eg, cerebrovascular ischemic events) but not systematically. In addition, postmortem analysis in patients with GCA cannot guarantee an acute state of inflammation of the analyzed tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Still, at least intradural involvement of the vertebral arteries was reported in single postmortem cases. 5,6 Another postmortem study reported 1 of 4 patients with GCA with generalized vasculitis in large and small cerebral vessels. 19 Accordingly, studies focused on primary or secondary vasculitis with cerebral involvement generally do not include patients with a GCA diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] DHA'da kafa içi damarlar›n tutulumu nadirdir. [23][24][25] DHA'da geçici iskemik atak, bafl dönmesi, iflitme kayb› ve inme görülebilir. Bunun en s›k nedeni vertebral arterlerin tutulumu veya internal karotis arterin ekstra dural lezyonlar›d›r.…”
Section: Klinik Bulgularunclassified
“…Bunun en s›k nedeni vertebral arterlerin tutulumu veya internal karotis arterin ekstra dural lezyonlar›d›r. [23,[25][26][27] DHA nadir olarak, dil a¤r›s› ve dil enfarktüsü, bo¤az a¤r›s›, uygunsuz ADH sendromu, [28,29] meme tümör benze-ri kitle, [30] mononöritis multipleks, [27] sensorinöral iflitme kayb›, [31] dizartri, [32] mezenterik iskemiye [32] neden olabilir.…”
Section: Klinik Bulgularunclassified